2020
DOI: 10.11152/mu-2652
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography techniques in the preoperative diagnosis of parotid gland tumors – an updated review of the literature

Abstract: Preoperative diagnosis of parotid tumors plays a crucial role in selecting and planning the surgical treatment. Ultrasound (US) with its modern techniques can contribute to the differential diagnosis of parotid tumors. This paper aims to achieve a comprehensive review of the ultrasound techniques used in the differential diagnosis of parotid tumors, based on the latest literature data. Considering that most parotid gland tumors are located in the superficial lobe, US is frequently the first imaging technique u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…They concluded that there was a correlation between the micro-and the macro-vascularization of the lesions respectively evaluated with CEUS and Color-Doppler US, but the predictive value of each single technique was not so effective and a multiparametric assessment was required to increase the specificity and PPV in the diagnosis of malignant parotid lesions and the sensitivity in the differential diagnosis between pleomorphic adenomas and Warthin's tumors [37]. Another recent review confirmed that MPUS, specially if includes CEUS, enables the differential diagnosis of parotid tumors [1,20].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…They concluded that there was a correlation between the micro-and the macro-vascularization of the lesions respectively evaluated with CEUS and Color-Doppler US, but the predictive value of each single technique was not so effective and a multiparametric assessment was required to increase the specificity and PPV in the diagnosis of malignant parotid lesions and the sensitivity in the differential diagnosis between pleomorphic adenomas and Warthin's tumors [37]. Another recent review confirmed that MPUS, specially if includes CEUS, enables the differential diagnosis of parotid tumors [1,20].…”
Section: Discussionmentioning
confidence: 99%
“…The following patterns were considered at the evaluation with baseline ultrasound: 1) suspected malignant lesions: nodular appearance, irregular or frankly infiltrating margins, heterogeneous hypoechoic structure, calcifications and hypo-anechoic necrotic-hemorrhagic internal areas, associated regional lymphadenopathy [1,15]; 2) pleomorphic adenoma: homogeneous, lobulated, hypoechoic structure with posterior wall enhancement, with or without calcifications, poor vascularization [1,16]; 3) Warthin's tumor: oval, hypoechoic mass, capsulated with anechoic and hypervascularized areas [1,17,18].…”
Section: B-mode Us and Color-doppler Usmentioning
confidence: 99%
See 3 more Smart Citations